Laura Chianese - Methanol Synthesis from CO₂ and Hydrogenation over Cu-ZnO-black TiO₂ Catalysts: Effect of Copper Loading and ZnO Promotion (Jornada de Jóvenes Investigadores del I3A, 2025)
Methanol Synthesis from CO₂ and Hydrogenation over Cu-ZnO-black TiO₂ Catalysts: Effect of Copper Loading and ZnO Promotion